PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA GENIALLY TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SEKOLAH DASAR - Putri, Hilma Innayah; Suwangsih, Erna; Hikmatunisa, Nenden Permas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the Discovery Learning model assisted by the Genially digital media on elementary school students’ critical thinking skills in Science and Social Science (IPAS) learning. The study employed a quasi-experimental method with a nonequivalent control group design. The research sample consisted of 23 fourth-grade students from SDN 1 Tegalmunjul Purwakarta in both the experimental and control classes. The research instrument was a Pretest and Posttest essay designed to assess five critical thinking indicators based on Ennis’ theory. The results showed that students taught using the Discovery Learning model with Genially media showed a significant improvement in critical thinking skills compared to those taught using the Cooperative Learning model. Data analysis using T-Tests and N-Gain scores indicated moderate to high improvement. It is concluded that the Discovery Learning model with Genially media is effective in enhancing students’ critical thinking skills in IPAS learning.